IMPROVING THE STUDENTS’ ABILITY IN READING NARRATIVE TEXT THROUGH SERIES OF PICTURE AT GRADE TEN OF SMA KAMPUS PEMATANGSIANTAR - Siahaan, Desta Gloria; Yulita, Delti (English Study Program, Faculty of Teacher Training and Educational Sciences, Universitas Timor, 2021)
This research is a descriptive quantitative research that deals with the use of series of to improve the students’ ability in reading narrative text at the grade ten of SMA Kampus Pematangsiantar. The research problem of this study were (1) how is the implementation of picture series in teaching narrative reading of narrative text to grade ten of SMA Kampus Pematangsiantar. The writer applies the theories of Lado (1986), Harmer (1998), Alderson (2000), Nunan (2003), Patel (2008) and Siahaan (2011) to analyze the understanding of reading. The research methodology used the essay test as the instrument of collecting the data by applying pre test, treatment and post test. The result of this study showed that the reading ability of the students after using picture series to teach reading narrative text to grade ten of SMA Kampus Pematangsiantar is significantly improved.